Determinants of the decision to adopt Islamic finance: evidence from Oman - Yasmeen Al Balushi; Stuart Locke; Zakaria Boulanouar (ISRA International Journal of Islamic Finance, 2019)
Purpose: Small and medium enterprises' (SMEs) capital structure and financial policies are important areas of policy concern. Only a limited number of studies on capital structure have, however, been conducted on SMEs, and this deficiency is particularly evident when investigating what influences funding decisions around Islamic finance. This paper accordingly aims to investigate whether Omani SME owner-managers' intention to adopt Islamic finance is influenced by their knowledge of Islamic finance, their own characteristics and/or their firms' characteristics. Design/methodology/approach - The authors administered a questionnaire survey via face-to-face interviews to 385 SME owner-managers operating in Muscat, Oman's capital city. The Kruskal-Wallis oneway analysis of variance (ANOVA) non-parametric test was used to analyse the questionnaire survey data. Findings - The findings indicate that while SME owner-managers' Islamic financial knowledge and personal characteristics do influence their intention to adopt Islamic finance, their firms' characteristics have no significant influence on SME owner-managers' decisions to accede to Islamic financing. Research limitations/implications - The research's first limitation is that it gathered data from SME owner-managers in Muscat only. Future studies could survey a wider sample of Omani SME ownermanagers. Second, the study's findings cannot be generalised to large and public firms, as the sample includes owner-managers of SMEs only. Finally, there is a need to investigate other factors such as nonfinancial and behavioural factors, which were not explored in the present study, but which may influence SME ownermanagers' Islamic financial decisions. Originality/value - Theoretical and empirical studies on capital structure have focused primarily on large listed firms. Only a few studies have paid attention to the capital structure of SMEs, particularly in the context of an emerging market such as Oman. This gap in the literature is mostly evident when investigating the factors that influence the funding decision towards Islamic financing in a country, such as Oman, where Islamic finance represents a new banking sector offering.
Keywords: 330; Islamic financial decisions; SMEs; Oman; Owner-manager's Islamic financial knowledge; Firm's characteristics